Environmental Care Behavior through Waste Bank (Study at Teratai Waste Bank Pondok Pucung Sub-district, Pondok Aren District, South Tangerang City) - Anjani, Alfitra Dewi; Budiaman, Budiaman; Hidayaht, Achmad Nur (Advances In Social Humanities Research, 2024)
This study investigates the effectiveness of Waste Bank Lotus in enhancing community environmental awareness in South Tangerang, Indonesia. With the escalating waste generation in tandem with population growth, waste management has emerged as a critical issue exacerbated by limited landfill capacity. The Lotus Waste Bank initiative seeks to mitigate these challenges by instilling environmental consciousness among residents. Employing descriptive research methods, including observation, interviews, questionnaires, documentation, and literature review, data were gathered from 63 participants selected through purposive sampling. The results reveal that Waste Bank Lotus has successfully raised community awareness regarding environmental issues, fostered responsible behaviors in waste, water, and energy management, and adopted eco-friendly products. Moreover, various factors, including intention, community support, personal autonomy, access to information, and favorable conditions, influence community environmental behavior. Environmental awareness through waste banks entails building awareness, motivation to act, evaluation, attempted implementation, and integration into daily routines. This research underscores the pivotal role of waste banks in promoting sustainable waste management practices and cultivating a culture of environmental stewardship within communities.